Optimization of electro-blown polysulfone nanofiber mats for air filtration applications - Sarac, Zuleyha; Kilic, Ali; Tasdelen-Yucedag, Cigdem (Wiley, 2023)
Durable, robust, and hydrophobic air filtration media was produced via electro-blow spinning (EBS) technique using polysulfone (PSU) due to its superior properties. To our knowledge, this is the first optimization study of PSU nanofiber production via EBS technique for air filtration applications. Concentration, air pressure, and voltage were determined as independent variables for the optimization based on smaller is the better approach of Taguchi Design of Experiment. The optimized values which supplied the smallest average fiber diameter (AFD) possible were obtained as 13 wt% PSU, 3 bar, and 7.5 kV. The AFD of the sample obtained from the confirmation experiment was calculated as 105 +/- 34 nm. Surface morphologies, porosity values, and wettability behaviors of the samples were investigated by using scanning electron microscopy, gravimetric method, and water contact angle measurements, respectively. PSU nanofiber mats exhibited superhydrophobic behavior (water contact angle values up to 159.8 degrees) which is important for various separation processes. Samples prepared at different deposition times (15, 30, 45, and 60 min) were investigated in terms of particle capture efficiency and pressure drop. The 0.3 mu m particle filtration efficiency was found to be 98.09% at an expense of 202 Pa pressure drop which would be suitable for various respiratory and HVAC filter applications.
Keywords: air filtration; electro-blow spinning; nanofiber; polysulfone; Taguchi optimization